Nitrate and ammonium differ in their impact on δ13C of plant metabolites and respired CO2 from tobacco leaves. Issue 1 (2nd January 2021) - Ghiasi, Shiva; Lehmann, Marco M.; Badeck, Franz-W.; Ghashghaie, Jaleh; Hänsch, Robert; Meinen, Rieke; Streb, Sebastian; Hüdig, Meike; Ruckle, Michael E.; Carrera, Dániel Á.; Siegwolf, Rolf T. W.; Buchmann, Nina; et al.
ABSTRACT: The carbon isotopic composition (δ 13 C) of foliage is often used as proxy for plant performance. However, the effect of N O 3 – vs. N H 4 + supply on δ 13 C of leaf metabolites and respired CO2 is largely unknown. We supplied tobacco plants with a gradient of N O 3 – to N H 4 + concentration ratios and determined gas exchange variables, concentrations and δ 13 C of tricarboxylic acid (TCA) cycle intermediates, δ 13 C of dark-respired CO2, and activities of key enzymes nitrate reductase, malic enzyme and phosphoenolpyruvate carboxylase. Net assimilation rate, dry biomass and concentrations of organic acids and starch decreased along the gradient. In contrast, respiration rates, concentrations of intercellular CO2, soluble sugars and amino acids increased. As N O 3 – decreased, activities of all measured enzymes decreased. δ 13 C of CO2 and organic acids closely co-varied and were more positive under N O 3 – supply, suggesting organic acids as potential substrates for respiration. Together with estimates of intra-molecular 13 C enrichment in malate, we conclude that a change in the anaplerotic reaction of the TCA cycle possibly contributes to 13 C enrichment in organic acids and respired CO2 under N O 3 – supply. Thus, the effect of N O 3 – vs. N H 4 + on δ 13 C is highly relevant, particularly if δ 13 C of leaf metabolites or respiration is used as proxy for plant performance.